Issues in cataloging Islamic collection - Suja', Balqis (2002)
This is a 20 minutes presentation on common problems in organizing and cataloguing the Arabic and Islamic materials, their characteristics, especially on the matter of romanization, what type of record best serve the library users, which bibliographic utilities or ILS able to handle roman and Arabic record, adherence to standards, training needs, Arabic cataloguing manual and support for bibliographic control. A brief technical services operation at IIUM Library with regards to acauisitions, cataloguing, gift and exchange and physical processing were presented.